Optimization of Component Transportation Costs with Narrow Service Time Window and Heterogenous Vehicle Capacity - Erika Fatma; Supardi Manurung (Jurnal Rekayasa Sistem & Industri, 2020)
Transportation costs are one of the largest cost components in distribution activities.Transportation costs can be reduced by improving distribution routes. The aims of this articleare to minimize transportation costs by determining vehicle assignments and routing forheterogeneous vehicles. The constrains that considered are the number and capacity of thevehicle, fuel consumption, service time at the company and at customers plant. Totaltransportation costs are considered as vehicle fixed costs, fuel costs, and material handling costs.CVRPTW is applied to the problem of assigning and determining vehicle routes of plasticcomponent companies that supply plastic components for various manufacturing companies inthe Greater Jakarta area. CVRPTW can reduce transportation costs in the company while stillmeet all applicable constraints. CVRPTW reduced the number of vehicles used from theprevious 6 vehicles to 5 vehicles. Total transportation costs for all shipping routes are Rp.4,563,620. This cost is lower than the company costs of Rp. 4,694,100, this routing problemreduces transportation costs by 8% of the initial cost.